2023
DOI: 10.1177/10482911231189503
|View full text |Cite
|
Sign up to set email alerts
|

Active Surveillance of Engineered Stone Workers Facilitates Early Identification of Silicosis: A Discussion of Surveillance of Occupational Lung Diseases

Sheiphali A. Gandhi,
Amy Heinzerling,
Jennifer Flattery
et al.

Abstract: Silicosis in workers exposed to respirable crystalline silica while fabricating engineered stone products is an emerging respiratory health issue. We describe silicosis in engineered stone workers in California and examine clinical features by the source of identification. Cases were identified passively using hospital-based patient discharge data or actively through outreach and medical testing following enforcement investigation. Outcomes were examined based on the source of case identification. We identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In addition to compliance with and enforcement of regulatory standards, medical surveillance of engineered stone workers is urgently needed, as well as public health reporting of cases of silicosis. A recent subsample analysis of the California silicosis cases found that cases identified through active medical surveillance and public health outreach had less severe, earlier-stage disease than cases identified passively through hospital discharge data . That analysis also highlighted the critical importance of connecting public health reporting of occupational diseases by clinicians with workplace exposure monitoring and surveillance efforts.…”
mentioning
confidence: 99%
“…In addition to compliance with and enforcement of regulatory standards, medical surveillance of engineered stone workers is urgently needed, as well as public health reporting of cases of silicosis. A recent subsample analysis of the California silicosis cases found that cases identified through active medical surveillance and public health outreach had less severe, earlier-stage disease than cases identified passively through hospital discharge data . That analysis also highlighted the critical importance of connecting public health reporting of occupational diseases by clinicians with workplace exposure monitoring and surveillance efforts.…”
mentioning
confidence: 99%
“…The case of workers, disproportionately Latino, who cut engineered stone for countertops is regrettably similar. In Active Surveillance of Engineered Stone Workers Facilitates Early Identification of Silicosis: A Discussion of Surveillance of Occupational Lung Diseases, 7 Gandhi et al argue for active surveillance of lung diseases such as silicosis, especially found in workers who cut engineered stone for countertops. The authors report that 89% of the cases identified were Latino workers.…”
mentioning
confidence: 99%